Gaya Hidup Mahasiswi Konsumtif Dalam Penggunaan Produk Kecantikan Pada Mahasiswi Universitas Negeri Gorontalo - Fadli, Desy; Ibrahim, Ridwan; Hatu, Dewinta Rizky R. (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The lifestyle of female students in using beauty products is strongly influenced by their view of themselves and their surroundings. They tend to spend a lot of time and money buying popular or viral products. The method used in this research is a qualitative method using a descriptive approach. This data collection technique uses observation, interviews and documentation techniques. This study shows that: First, the consumptive behavior of female students is based on their dissatisfaction in owning beauty products. Female students prefer to collect certain beauty brands so they look beautiful and they don't care about expenses or prices that are so expensive, the most important thing is that curiosity and a sense of wanting to own these products are conveyed and secondly, the factors that influence female students in choosing beauty products are factors social media, friend factors, and personal factors.